ANALISIS VALUASI NILAI SAHAM PERUSAHAAN INDUSTRI PULP & PAPER MENGGUNAKAN METODE DISCOUNTED CASH FLOW VALUATION DAN RELATIVE VALUATION UNTUK PENGAMBILAN KEPUTUSAN PERIODE 2015-2019 - Johannes Kristian Siregar (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
This study aims to determine how much the intrinsic value of PT. Indah Kiat Pulp & Paper Tbk. (INKP), Tjiwi Kimia Paper Factory Tbk. (TKIM) and Fajar Surya Wisesa Tbk. (FASW) listed on the IDX in 2015-2019 where the stock valuation is calculated using the Dividend Discount Model, Free Cashflow to Equity and Price Book Value methods to determine whether the company's stock is undervalued or overvalued, making the right decisions for potential investors based on value. intrinsic value and knowing which method is the most accurate. The sample in this study were three companies that had complete financial statements and distributed dividends during the research year and had the most significant spike in stock prices. Data collection techniques in this study using purposive sampling technique and the data used is secondary data. The conclusion in this study is that in general, INKP and TKIM stocks are undervalued and FASW is in overvalued condition. The most accurate stock valuation method in this study is the Price Earning Ratio because it has the smallest RMSE value.